Fluctuating Disinhibition: Implications for the Understanding and Treatment of Alcohol and Other Substance Use Disorders - Jones, Andrew; Christiansen, Paul; Nederkoorn, Chantal; Houben, Katrijn; Field, Matt (Frontiers in Psychiatry, 2013)
Disinhibition is present in various maladaptive behaviours, including substance use disorders. Most previous research has assumed that disinhibition is a psychological construct that is relatively stable within individuals. However, recent evidence suggests that the ability to inhibit behaviour fluctuates in response to environmental and psychological triggers. In this review we discuss some of the factors that cause (dis)inhibition to fluctuate, we examine whether these fluctuations contribute to subjective craving and substance consumption, and we ask if they might increase the risk of relapse in those who are attempting to abstain. The research that we discuss has furthered our understanding of the causal relationships between disinhibition and substance use disorders, and it also highlights opportunities to develop novel treatment interventions. We conclude that substance misusers and their therapists should be made aware of the triggers that can cause disinhibition to fluctuate, and we highlight the need for more research to investigate the effectiveness of inhibitory control training in clinical settings.